Calcium and sodium ions synergistically enhance the thermostability of a maltooligosaccharide-forming amylase from Bacillus stearothermophilus STB04. (15th June 2019) - Pan, Sihui; Gu, Zhengbiao; Ding, Ning; Zhang, Ziqian; Chen, Dianning; Li, Caiming; Hong, Yan; Cheng, Li; Li, Zhaofeng
Highlights: Bst-MFAse, an amylase, hydrolyzes starch into functional maltooligosaccharides. Ca 2+ and Na + synergistically enhance the thermostability of Bst-MFAse at 80 °C. Protein modeling reveals an important Ca 2+ –Na + –Ca 2+ binding site in its structure. Ca 2+ and Na + synergistically protect the secondary structure of Bst-MFAse. Ca 2+ and Na + synergistically protect the tertiary structure of Bst-MFAse. Abstract: Maltooligosaccharide-forming amylases (MFAses) are promising tools for a variety of food industry applications because of their ability to hydrolyze starch into maltooligosaccharides. However, high thermostability is a key requirement for enzymes used in these applications. In this work, we investigated the effect of Ca 2+ and Na + on the thermostability of an MFAse from Bacillus stearothermophilus (Bst-MFAse). The results showed that Ca 2+ and Na + synergistically prolong the half-life of Bst-MFAse. The most significant improvement, which preserved 71.1% of initial activity after incubation at 80 °C for 180 min, was achieved by adding 10 mM Ca 2+ and 40 mM Na + simultaneously. The increase in Bst-MFAse thermostability imparted by the addition of Ca 2+ and Na + may be associated with an important Ca 2+ –Na + –Ca 2+ triad structure. This study provides an effective way to enhance the thermostability of Bst-MFAse and related enzymes.